2009
DOI: 10.1016/j.pain.2009.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Cross-inhibition between native and recombinant TRPV1 and P2X3 receptors

Abstract: Small- to medium-sized neurons in the dorsal root ganglion (DRG) convey nociceptive information to the spinal cord. The co-expression of TRPV1 receptors (sensitive to vanilloids, heat and acidic pH) with P2X(3) receptors (sensitive to extracellular ATP) has been found in many DRG neurons. We investigated whether the co-activation of these two receptor classes in small-diameter cells leads to a modulation of the resulting current responses shaping the intensity of pain sensation. The whole-cell patch clamp meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 57 publications
1
41
0
1
Order By: Relevance
“…In agreement with previous studies in rat lumbar DRG neurons (16,41,48), the present work demonstrates that a substantial proportion of mouse PN colorectal afferent somata coexpress TRPV1 with P2X3. Previously, we reported deficits in colorectal mechanosensation and sensitization with single deletion of either TRPV1 or P2X3 (19,20,39).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous studies in rat lumbar DRG neurons (16,41,48), the present work demonstrates that a substantial proportion of mouse PN colorectal afferent somata coexpress TRPV1 with P2X3. Previously, we reported deficits in colorectal mechanosensation and sensitization with single deletion of either TRPV1 or P2X3 (19,20,39).…”
Section: Discussionsupporting
confidence: 93%
“…The results suggest an additive, if not greater than additive, attenuation of afferent response to stretch by simultaneous antagonism of both channels. This may be secondary to a combined effect of two independent processes, or it may indicate an interaction that could be mediated through shared Ca 2ϩ -dependent signaling cascades (10,21,33,36,47,55) or modulatory conformational spread (4) via direct physical association of TRPV1 and P2X3 as demonstrated previously (41). Importantly, this combined antagonist/agonist experiment additionally confers pharmacological validity to the selectivity of the drugs used (e.g., TNP-ATP has effects only on REs that respond to ␣,␤-meATP).…”
Section: Discussionmentioning
confidence: 74%
“…Similar experiments have now been repeated with several ion channel combinations showing that cross inhibition between P2X receptors and members of the nicotinic receptor-like family are common (Barajas-Lopez et al, 1998; Barajas-Lopez et al, 2002; Boue-Grabot et al, 2003; Boue-Grabot et al, 2004a; Boue-Grabot et al, 2004b). Most recently, functional interactions have been reported for P2X receptors and acid sensing ion channels (ASIC) (Birdsong et al, 2010) as well as between P2X3 receptors and TRPV1 channels (Stanchev et al, 2009). We comment here on general themes that emerge.…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…Accordingly, capsaicin has been shown to inhibit several different ion channels in DRG neurons, and for inhibition of KCNQ channels (Zhang et al, 2011) and for inhibition of TRPA1 (Akopian et al, 2007) inclusion of PI(4,5)P 2 in the whole cell patch pipette alleviated capsaicin-induced inhibition. For inhibition of Voltage-gated Ca 2+ channels (Wu et al, 2006), P2X channels (Stanchev et al, 2009), HCN channels (Kwak, 2012) and for voltage gated Na + channels (Liu et al, 2001), the role of phosphoinositides has not been tested, see details at the discussion of the individual channels. Local capsaicin evokes intense burning pain, but paradoxically, it is also used as a local analgesic, because of the desensitization of the nociceptor neurons, which includes many processes, including desensitization of the channel itself, and potentially inhibition of some of the other ion channels described here (Szallasi and Blumberg, 1999).…”
Section: Activation Of Plc By Ca2+ Influxmentioning
confidence: 99%
“…It was shown that in rat DRG neurons activation of P2Y2 receptors inhibit P2X3 via PI(4,5)P 2 depletion (Mo et al, 2013). Capsaicin also inhibits P2X3 in TRPV1 expressing cells (Stanchev et al, 2009), and in rat DRG neurons (Piper and Docherty, 2000) but the involvement of phosphoinositides were not examined.…”
Section: Ligand Activated and Chemosensitive Ion Channelsmentioning
confidence: 99%